Nieobecność religioznawstwa w polskiej edukacji szkolnej - Iwanicki , Juliusz (Studia Edukacyjne, 2019)
The article analyzes the problem of the absence of religious studies in Polish school education. The first part explains the status of religious studies as a discipline. In the main part, the school core curriculum in the primary school was analyzed with respect to the humanities. Then, reference was made to the presence of religion in school as catechesis. The final part presents earlier attempts to introduce religious studies to schools as well as their own ideas on this issue.